The Effectiveness of Cognitive Behavioral Therapy on Emotional Reactivity and Negative Automatic Thoughts in Lower Secondary School Female Students - Gholbeyki Mansourkouhi, Fatemeh; Ebrahimi, Sedighe; Mousavi, Seyedeh Sakineh; Badelleh, Zahra; Norouzi Chamani, Shiva (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The present study aimed to examine the effectiveness of Cognitive Behavioral Therapy (CBT) on emotional reactivity and negative automatic thoughts in lower secondary school female students.Materials and Methods: This study employed a quasi-experimental and applied research design using a pre-test–post-test design with a control group. The statistical population consisted of all lower secondary school female students in Fuman County during the 2024–2025 academic year. The study sample included 30 students, who were selected using a purposive sampling method and were randomly assigned to an experimental group (15 students) and a control group (15 students). The research instruments included the Emotional Reactivity Scale developed by Nock et al. (2008) and the Automatic Thoughts Questionnaire developed by Hollon and Kendall (1980). Multivariate Analysis of Covariance (MANCOVA) and Univariate Analysis of Covariance (ANCOVA) were used to analyze the data and test the research hypotheses.Findings: The findings indicated that there was a statistically significant difference between the intervention group and the control group in terms of mean scores on emotional reactivity and negative automatic thoughts (p < .001).Conclusion: Overall, the results demonstrated that Cognitive Behavioral Therapy led to a reduction in emotional reactivity and negative automatic thoughts among the students.